Design of split ring resonator filters for interference suppression in UWB - Leow, Chai Ling; Soh, Ping Jack; Carpenter, S.; Azremi, Abdullah Al Hadi; Ezanuddin, A. A. M. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/